Comparative study of tensile properties of kenaf bast and core fibre reinforced unsaturated polyester composites - Ishak, Mohamad Ridzwan; Mohamed Yusoff, Mohd Zuhri; Salit, Mohd Sapuan; Leman, Zulkiflle; Abdul Manaf, Mohd Edeerozey; Othman, Intan Sharhida (2009)
Tensile properties of kenaf bast and core fibre reinforced unsaturated polyester composites were examined in this study. Composite of 5%, 10%, 20%, 30% and 40% weight of randomly chopped kenaf bast and core fibre were prepared. Tensile test was carried out in accordance to the ASTM D5083. The results showed that the optimal value to obtain the highest tensile strength was 20%. It also has been observed that the elongation at break for both bast and core fibre composites had decreased as the fibre content increases. It also can be noted that composites reinforced with kenaf bast fibre are found to have consistently higher tensile properties than kenaf core fibre composites.